Rural Nonfarm Activities and Agricultural Crop Production in Nigeria - Oseni, Gbemisola (2012)
Although most rural households are involved in the farm sector, the nonfarm sector has grown significantly in recent decades, and its role in rural development has become increasingly important. This article examines the effect of participation in nonfarm activities on crop expenses of farm households in Nigeria. The relationship is modeled using a nonseparable agricultural household model that suggests that participating in nonfarm activities can relax the credit constraints facing farm households and reduce risk thereby helping households improve farm production and smooth consumption over time. The results show that participation in nonfarm activities by Nigerian farmers has a positive and significant effect on crop expenses and in particular on payments for hired labor and inorganic fertilizers. Separate analysis of the six geopolitical zones in Nigeria indicates that it is in the South-South and South-East zones where nonfarm participation appears to induce more hiring of labor. The results support the hypothesis that nonfarm participation helps relax liquidity constraints but suggests how that liquidity is used is zone-specific. In general, the results also indicate that liquidity is used more to pay for inputs into staple production as opposed to cash crops.